2012
DOI: 10.4236/ojepi.2012.21001
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and rate of infections in diabetes mellitus patients with diabetes ketoacidosis in Penang, Malaysia

Abstract: Study aimed to determine the rate and prediction of infection in diabetes mellitus patients ≥ 18 year, with diabetic ketoacidosis (DKA). Retrospective cohort study design was adopted to achieve the objectives. Universal sampling technique was employed for data collection among Diabetes ketoacidosis patients, over a period of 3 years (Jan 2008-Dec 2010). Statistical package for social sciences used to analyze data. Over a 3-year period, total of 967 admissions were identified. Of it, 112 (11.6%) with no infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
1
5
1
Order By: Relevance
“…However, there was an association between both pH and serum bicarbonate, and an elevated leucocyte count. 15 Our data corroborate the lack of correlation between neutrophilia and infection. The severity of DKA at presentation resulting in a proportionately higher total leucocyte count may contribute to the likelihood of antimicrobial prescription as clinicians may attribute this value to occult infection.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…However, there was an association between both pH and serum bicarbonate, and an elevated leucocyte count. 15 Our data corroborate the lack of correlation between neutrophilia and infection. The severity of DKA at presentation resulting in a proportionately higher total leucocyte count may contribute to the likelihood of antimicrobial prescription as clinicians may attribute this value to occult infection.…”
Section: Discussionsupporting
confidence: 85%
“…15,16 A study performed by Slovis et al 16 in 1987 on 153 patients reported a correlation between neutrophil band count >10% and infection, with a sensitivity of 100% and specificity of 80%. 15,16 A study performed by Slovis et al 16 in 1987 on 153 patients reported a correlation between neutrophil band count >10% and infection, with a sensitivity of 100% and specificity of 80%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations